Newspaper Editorials Show Few Regional Differences - Bramlett-Solomon, Sharon (Newspaper Research Journal, 2001)
This content analysis of 109 editorials revealed more similarities than differences in how Southern, Northern and Western newspapers characterized black church burnings. The findings call into question the assumptions that regional differences exist in portrayals of racial conflicts.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wNzM5NTMyOTAxMDIyMDA0MDQ